Radio emission of tidal disruption events from wind–cloud interaction. Issue 3 (17th March 2023) - Bu, De-Fu; Chen, Liang; Mou, Guobin; Qiao, Erlin; Yang, Xiao-Hong
ABSTRACT: Winds can be launched in tidal disruption event (TDE). It has been proposed that the winds can interact with the cloud surrounding the black hole, produce bow shocks, accelerate electrons, and produce radio emission. We restudy the wind–cloud interaction model. We employ the properties of winds found by the radiation hydrodynamic simulations of super-Eddington circularized accretion flow in TDEs. We can calculate the peak radio emission frequency, the luminosity at the peak frequency, and their time-evolution based on the TDEs wind–cloud interaction model. We find that the model predicted peak radio emission frequency, the luminosity at peak frequency, and their time evolution can be well consistent with those in TDEs AT2019dsg and ASASSN-14li. This indicates that in these two radio TDEs, the wind–cloud interaction mechanism may be responsible for the radio emission.